Validating the early corrosion sensing functionality in poly (ether imide) coatings for enhanced protection of magnesium alloy AZ31. (1st August 2018) - Mata, D.; Scharnagl, N.; Lamaka, S.V.; Malheiro, E.; Maia, F.; Zheludkevich, M.L.
Graphical abstract: Highlights: Bifunctional coating is proposed to enhance the service life of corrosion susceptible AZ31 alloy. The pH changes following corrosion outbreak trigger both corrosion sensing and self-healing functionalities. Observations evidence correlation between kinetics of color signaling and corrosion activity. Abstract: This work reports on the validation studies of early corrosion sensing poly ether imide (PEI) coatings with incorporated pH-sensing phenolphthalein loaded silica nano-sized capsules (SiNCs-PhPh) on AZ31 magnesium alloys. Immersion and drop tests validated the high sensing accuracy and PhPh color-signaling reproducibility of the coatings upon onset of corrosion. This behavior is correlated to the homogeneous dispersion of SiNC particle agglomerates confirmed by 3D Raman mapping and SEM analysis. Complementary differential video imaging technique (DVIT) assisted by electrochemical impedance spectroscopy (EIS) investigations provided clues for a good correlation between the kinetics of color signaling and the corrosion activity. Mechanistic insights into the pH-sensing/color-signaling functionality in PEI coatings are suggested.